2016
DOI: 10.3389/fnins.2016.00132
|View full text |Cite
|
Sign up to set email alerts
|

Animal Models of Tourette Syndrome—From Proliferation to Standardization

Abstract: Tourette syndrome (TS) is a childhood onset disorder characterized by motor and vocal tics and associated with multiple comorbid symptoms. Over the last decade, the accumulation of findings from TS patients and the emergence of new technologies have led to the development of novel animal models with high construct validity. In addition, animal models which were previously associated with other disorders were recently attributed to TS. The proliferation of TS animal models has accelerated TS research and provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…While recent studies in rodents has demonstrated that interactions between the PT and motor cortex determine where (PT) and when (motor cortex) tics will occur ( Israelashvili and Bar-Gad, 2015 ; Yael et al, 2016 ), our results also support an extended network model and replicate previous findings showing significant activation/abnormality of the cerebellum during the production of tics ( Bohlhalter et al, 2006 ; Lerner et al, 2007 ; Stern et al, 2000 ), and that the cerebellum is an integral part of the tic generating network. The cerebellum is known to have direct and indirect connections with the BG via intralaminar thalamic nuclei ( Hoshi et al, 2005 ).…”
Section: Discussionsupporting
confidence: 90%
“…While recent studies in rodents has demonstrated that interactions between the PT and motor cortex determine where (PT) and when (motor cortex) tics will occur ( Israelashvili and Bar-Gad, 2015 ; Yael et al, 2016 ), our results also support an extended network model and replicate previous findings showing significant activation/abnormality of the cerebellum during the production of tics ( Bohlhalter et al, 2006 ; Lerner et al, 2007 ; Stern et al, 2000 ), and that the cerebellum is an integral part of the tic generating network. The cerebellum is known to have direct and indirect connections with the BG via intralaminar thalamic nuclei ( Hoshi et al, 2005 ).…”
Section: Discussionsupporting
confidence: 90%
“…Underpinning the circuit underlying such a result was not the focus of this study, but it connects with the call for standardization of the preclinical model for TS due to the still remaining confusion between these two motor phenomena (tics and stereotypies) often used in the tic-model literature with an interchangeable meaning ( 36 ). Tic-like movements in animal models are often confused with stereotypies, though they are separated clinical entities.…”
Section: Discussionmentioning
confidence: 96%
“…The cause of tic production and the resting state of the brain in TS has been explored with neurophysiology and structural/functional imaging (each using many modalities), small scale but influential postmortem and transcriptome work34 and increasingly relevant animal models 35. There is very clearly a neurological substrate but it is not yet fully understood.…”
Section: Abbreviated Neurobiology Of Tsmentioning
confidence: 99%